Digital transformation and human capital in retail banking in South Africa - Lediga, Katlego (University of the Witwatersrand, Johannesburg, 2022)
The digital transition is disruptive because it brings great change along with it. The banking business is being reshaped by powerful forces like but not limited to expectations from customers, technological abilities, legislative requirements, demographic trends, and economics. These are all combined to create a pressing need for change. Banks must anticipate these problems and retool in order to succeed in the future age. Banks must not only meet today's demands but also drastically innovate and restructure themselves in order to be competitive in the future. In the banking industry, digital transformation is a continual process involving both the micro and macro environment through revamping internal procedures and systems. Digital transformation occurs for a variety of reasons, including serving rural areas without branch locations, differentiating from competitors, and lowering operational expenses. In any event, there are many reservations about digital technologies' acceptability. Most people's computers or mobile phones are now used to conduct a substantial proportion of banking transactions. The variety of options, as well as the time and cost savings, and the ease of use of these applications, ensure that they continue to outperform traditional banking channels like bank branches. (Kitsios & Giatsidis, 2021) The purpose of the study is to ascertain how human capital in the form of business units and line managers within retail banks responded to the technological disruptions within the South African context. The objective of this research is to provide an overview of the shift from a workplace that does not rely on technology to one that is heavily reliant on technological integration to achieve operational needs. It will examine the repercussions of process automation migrations, as well as how this affects attrition rate and retention as human capital tries to adjust to such a radical change
A research article submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Business Administration Johannesburg, March 202
Keywords: Human capital; Retail banking; Up skilling; Automation; Digitazation; UCTD; SDG-8: Decent work and economic growth